2022
DOI: 10.54847/cp.2022.04.16
|View full text |Cite
|
Sign up to set email alerts
|

Incidental appendectomy in surgical treatment of ileocolic intussusception in children. Is it safe to perform?

Abstract: Background. Surgical treatment of ileo-colic intussusception (ICI) has been reported as the second cause of emergency laparotomy in children. The performance of incidental appendectomy after surgical reduction is currently controversial. The aim is to analyse the outcomes of performing incidental appendectomy after surgical ICI reduction with or without associated bowel resection.Materials and methods. A retrospective study was performed in patients with ICI episodes, who underwent surgical treatment in our in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, any excess risk of SSI is often associated with an extended hospital stay, thus imposing a severe financial pecuniary burden on the health-care system [39,40]. Among a cohort of children undergoing surgery for acute appendicitis, Delgado-Miguel et al found that obesity conferred almost two times higher risk for SSI [12 ▪ ]. Similar findings have been reported by other researchers analyzing children undergoing similar surgical procedures [41,42].…”
Section: Perioperative Implications Of Pediatric Obesitymentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, any excess risk of SSI is often associated with an extended hospital stay, thus imposing a severe financial pecuniary burden on the health-care system [39,40]. Among a cohort of children undergoing surgery for acute appendicitis, Delgado-Miguel et al found that obesity conferred almost two times higher risk for SSI [12 ▪ ]. Similar findings have been reported by other researchers analyzing children undergoing similar surgical procedures [41,42].…”
Section: Perioperative Implications Of Pediatric Obesitymentioning
confidence: 56%
“…It is therefore essential that clinicians who endeavor to address these surgical needs be equipped with the most up-to-date empirical data on the opportunity to improve the care for the subset of children who are obese. Obese children are at an increased risk for chronic health conditions and several complications specific to the perioperative period, including respiratory adverse events, infections, bleeding events [9–11,12 ▪ ,13]. This excess risk of perioperative morbidity makes it imperative that childhood obesity be adequately screened during the preoperative assessment [14].…”
Section: Introductionmentioning
confidence: 99%